The survival and safety of metastatic hepatocellular carcinoma treated with lenalidomide as second-line therapy: a case report and review of the literature - Tao Li; Ying Zhao; Keren Li; Gong Li; Guangxin Li (Frontiers in Oncology)
BackgroundHepatocellular carcinoma (HCC) is a highly lethal and invasive cancer. Targeted and immunotherapies are the primary treatment options for unresectable advanced HCC. There are no recognized and consistent systemic follow-up treatments for patients with HCC who experience disease progression after first-line targeted therapies and immune checkpoint inhibitors (ICIs). According to a few studies, lenalidomide is an immunomodulatory drug that has the potential to be an effective treatment for patients who have progressed after treatment with targeted drugs and ICIs.Case summaryThis article focuses on a patient with HCC whose disease progressed after first-line targeted therapy and ICI therapy combined with lenalidomide as second-line therapy on the basis of the original targeted and ICI regimens, resulting in a favorable oncologic outcome with acceptable toxicity. The progression-free survival (PFS) of the patients in this study reached 3 years, which is much longer than that previously reported, and no progression has occurred thus far.ConclusionsThis case implies that in patients with hepatocellular carcinoma who have failed first-line targeted therapy and ICIs, targeted therapy and ICIs can be restarted with the addition of lenalidomide, with surprising results.